Perceptions on 'effective' head teacher's leadership within the Slovenian context - Roncelli-Vaupot, Silva (Management, 2013)
The paper presents some research findings about effective head teacher leadership within the Slovene post secondary school context which indicate the dimensions of head teacher leadership processes. The head teachers responses to a questionnaire indicating features of knowledge about leadership, which were captured in four interpretative categories, namely being, knowing, acting, and effecting. Furthermore, the findings of some case studies gave a funneled perspective on contextually bounded leadership knowledge. The present paper points to dimensions of and to the nature of knowledge about leadership and, moreover, to some dilemmas and questions about the ways in which knowledge about leadership could be understood and learned.
Keywords: knowledge; ravnatelji; school; Slovenia; Slovenija; srednje šole; šolstvo; uspešnost; vodenje; znanje